Third Generation Cryoballoon. Is It Better? A Meta-Analysis - Toorabally, Mohammad Bilaal; Brunet, Beatrice Chung Fat King; Chen, Minglong (Cardiology and Cardiovascular Medicine, 2018)
Cryoablation for the isolation of the pulmonary veins is an established treatment for paroxysmal and persistent atrial fibrillation. The second generation cryoballoon improves the effectiveness of the procedure. Recently, a new third generation cryoballoon has been introduced with a 40% shorter tips which in theory, should impact the procedure efficacy and the real time visualization of pulmonary vein isolation due to a more proximal placement of the inner lumen mapping catheter. This meta-analysis analyses all the data available to compare the performance of the two latest generations of cryoballoons. Two investigators searched and analyzed all published literature comparing the second generation cryoballoon (Arctic fron Advance cryoballoon) to the third generation cryoballoon (Arctic front advance short tip cryoballoon) in Pubmed, Google Scholar and Cochrane library. 1625 patients from 6 published studies were included in this meta-analysis. 351 patients were in the third generation cryoballoon groups and 1243 patients were in the second generation cryoballoon groups. Analysis of the pooled data revealed that the third generation cryoballoon had a shorter procedure time and a higher freeze temperature. The fluoroscopy time was shorter in the second generation cryoballoons. As for real time recordings, it was more prevalent in the third generation group but this difference was not statistically significant. Cryoablation using the short tip third generation cryoballoon allows for a shorter procedure time and offers an enhanced ability to assess time to pulmonary vein isolation with equivalent procedural safety and efficacy.